Analisa Penyebab Indonesia Memindahkan Ibukota Ke Kalimantan Timur - hendra ikrar lubis (Jurnal Poros Politik, 2022)
Various problems that often occur in Jakarta and the disorderly arrangement of the city of Jakarta caused President Jokowi to announce that the location of the capital would be moved to East Kalimantan. Indonesia itself is not the first country to do this. Many foreign countries have done it and succeeded, of course this also needs to be imitated by Indonesia in order to build a better and more orderly capital city which is also one of the efforts to equalize development in Indonesia. So that in the future it is expected to be able to provide good in terms of economic and social